Development Of Arabic Calligraphy Learning Material Base On Self-Learning/ تطوير مادة تعليم الخط العربي على ضوء تعلم الذاتي - Muhamad Rizal Falaqi; Abdul Muntaqim Al Anshory (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Several educational institutions in the world have faced severe problems in Indonesia. The Indonesian government made the policy of limiting face-to-face learning activities to overcome the COVID-19 pandemic recently. Self-learning is one way to overcome problems that occur so that the learning process continues to run well, especially during this pandemic. The development of technology science also plays an essential role in education today. Efforts to include technology in education in the form of a textbook and video assistant based on self-learning are needed by students to improve their Arabic calligraphy writing skills. This study aims to produce textbooks and video assistants based on self-learning for Institute Sunan Giri Ponorogo students to help the learning process of Arabic calligraphy, which is easy and exciting and reveals viability and effectiveness. This research method was Borg and Gall's proposed research and development (RD) proposed by Borg and Gall. Then the data were analyzed quantitatively and qualitatively. This study indicates that the development of Arabic calligraphy learning material in a textbook and video assistant based on self-learning has been developed according to procedures. The results of testing the components of the Arabic calligraphy material show that: material experts assess product development as very good and feasible while learning design experts consider teaching material very good and feasible. Then, the test subjects assessed that the material learning components were excellent. The results of the product effectiveness test show that the Arabic calligraphy learning material based on self-learning was influential in helping the learning process that was easy and interesting.